First detection of extended-spectrum cephalosporin- and fluoroquinolone-resistant Escherichia coli in Australian food-producing animals. Issue 4 (December 2015) - Abraham, Sam; Jordan, David; Wong, Hui S.; Johnson, James R.; Toleman, Mark A.; Wakeham, David L.; Gordon, David M.; Turnidge, John D.; Mollinger, Joanne L.; Gibson, Justine S.; Trott, Darren J.
Highlights: First detection of extended-spectrum cephalosporin and fluoroquinolone-resistant Escherichia coli in Australian food-producing animals. These isolates resistant to critically important antimicrobials (CIAs) belong to internationally disseminated, multidrug-resistant zooanthroponotic clonal lineages. Frequency of resistance to CIAs among E. coli isolates causing clinical disease in Australian food-producing animals is defined. Abstract: This study aimed to define the frequency of resistance to critically important antimicrobials (CIAs) [i.e. extended-spectrum cephalosporins (ESCs), fluoroquinolones (FQs) and carbapenems] among Escherichia coli isolates causing clinical disease in Australian food-producing animals. Clinical E. coli isolates ( n = 324) from Australian food-producing animals [cattle ( n = 169), porcine ( n = 114), poultry ( n = 32) and sheep ( n = 9)] were compiled from all veterinary diagnostic laboratories across Australia over a 1-year period. Isolates underwent antimicrobial susceptibility testing to 18 antimicrobials using the Clinical and Laboratory Standards Institute disc diffusion method. Isolates resistant to CIAs underwent minimum inhibitory concentration determination, multilocus sequence typing (MLST), phylogenetic analysis, plasmid replicon typing, plasmid identification, and virulence and antimicrobial resistance gene typing. The 324 E. coli isolates from different sources exhibited a variable frequency of resistance to tetracycline (29.0–88.6%), ampicillin (9.4–71.1%), trimethoprim/sulfamethoxazole (11.1–67.5%) and streptomycin (21.9–69.3%), whereas none were resistant to imipenem or amikacin. Resistance was detected, albeit at low frequency, to ESCs (bovine isolates, 1%; porcine isolates, 3%) and FQs (porcine isolates, 1%). Most ESC- and FQ-resistant isolates represented globally disseminated E. coli lineages (ST117, ST744, ST10 and ST1). Only a single porcine E. coli isolate (ST100) was identified as a classic porcine enterotoxigenic E. coli strain (non-zoonotic animal pathogen) that exhibited ESC resistance via acquisition of bla CMY-2 . This study uniquely establishes the presence of resistance to CIAs among clinical E. coli isolates from Australian food-producing animals, largely attributed to globally disseminated FQ- and ESC-resistant E. coli lineages.